Politik Hukum Investasi Asing di Era Teknologi Digital - Ikraam, Akhmad (CV. Green Publisher Indonesia, 2025)
Digital transformation has changed the global economic landscape, including the patterns and directions of foreign direct investment (FDI). In Indonesia, the politics of foreign investment law are experiencing significant challenges and changes in responding to the flow of digital technology. This article analyzes how political and legal dynamics affect foreign investment regulations in the digital sector, as well as examines the extent to which these regulations are aligned with the needs of legal protection, digital sovereignty, and national competitiveness. With a juridical-normative approach and a critical analysis of current policies, this paper recommends the need for an adaptive, sovereign, and just legal politics in the face of digital disruption and foreign capital penetration. This study shows that investment openness without strengthening regulatory and institutional capacity will weaken Indonesia's bargaining position in the midst of global digital economy competition. Therefore, a political and legal direction is needed that not only supports investment growth, but also ensures the protection of citizens' digital rights, strengthening local infrastructure, and creating a sustainable digital ecosystem. The legal politics of foreign investment in the digital era must be based on the principles of justice, sovereignty, and sustainability to ensure equitable benefits for all components of the nation.